IDENTIFIKASI HAMA LALAT BUAH (Diptera: Tephritidae) PADA BEBERAPA VARIETAS TANAMAN MANGGA (Mangifera indica L.) DI KABUPATEN LOMBOK UTARA - Baiq Elaswari Arimbi; Hery Haryanto; Bambang Supeno (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2023)
This study aims to identify fruit flies that attack several varieties of mangoes in North Lombok District. The method used in this study is descriptive with survey techniques. Sampling was done by purposive random sampling. The implementation of the activity was carried out at 17 location points of the farmers' mango orchards in the North Lombok Regency. The identification results found two genera of fruit flies that attack seven varieties of mango, namely Bactrocera and Zeugodacus. The genus Bactrocera found 12 species, namely B. pallida, B. musae, B. correcta, B. pyrifoliae, B. dorsalis, B. neohumeralis, B. tuberculata, B. carambolae, B. opiliae, B. endiandrae, B. kandiensis and B. papayae, while the genus Zeugodacus found two species, namely Z. tau and Z. depressus. Bactrocera pyrifoliae is a fruit fly species that dominates mango varieties in North Lombok Regency with a dominance level of 0.59. One species of fruit fly was found belonging to the Quarantine Plant Pest Organisms (OPTK) group A2, namely Bactrocera musae. The diversity of fruit flies is 2.86, the abundance is 95.87%, and the dominance is 0.70.